2011
DOI: 10.1002/cncr.26374
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of acitretin versus placebo in patients at high‐risk for basal cell or squamous cell carcinoma of the skin (North Central Cancer Treatment Group Study 969251)

Abstract: BACKGROUND Chemoprevention with systemic retinoids has demonstrated promise in decreasing the incidence of new primary nonmelanoma skin cancers (NMSCs) in immunocompromised post-transplantation recipients. There is limited evidence for the use of systemic retinoids in the nontransplantation patient. To the authors’ knowledge, this is the first randomized controlled trial to assess the efficacy of acitretin as a chemopreventive agent in nontransplantation patients at high risk for NMSC. METHODS The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 26 publications
0
50
0
3
Order By: Relevance
“…Studies have shown mixed results in the risk reduction associated with acitretin. An RCT of 70 healthy patients with a history of NMSC found a 59% decrease odds of new NMSC in a 2-year period (acitretin: 54%, control: 74%; P = 0.13), although this did not meet statistical significance (83). A systemic review of 3 RCTs of acitretin in solid organ transplant recipients (SOTR) noted less CSCC development in patients receiving acitretin (84).…”
Section: Chemopreventionmentioning
confidence: 98%
“…Studies have shown mixed results in the risk reduction associated with acitretin. An RCT of 70 healthy patients with a history of NMSC found a 59% decrease odds of new NMSC in a 2-year period (acitretin: 54%, control: 74%; P = 0.13), although this did not meet statistical significance (83). A systemic review of 3 RCTs of acitretin in solid organ transplant recipients (SOTR) noted less CSCC development in patients receiving acitretin (84).…”
Section: Chemopreventionmentioning
confidence: 98%
“…In this regard, radiotherapy represents the best alternative to surgery, but cannot be advised as a rule given its side-effects and limitations. Although neoadjuvant use of oral retinoids (acitretin) may decrease the size of the tumour and reduce the overall tumour load in cases with multiple SCCs, there is currently a lack of supporting evidence from randomised studies [57].…”
Section: Treatment Of Primary Sitementioning
confidence: 99%
“…125 Oral retinoids (acitretin, oral retinol, and isotretinoin) also do not appear to reduce the incidence of BCC in those with a history of a keratinocyte cancer. [126][127][128][129] Limited evidence is available to support the utility of other agents, including oral nicotinamide, a-difluoromethylornithine, and celecoxib, in reducing the risk for keratinocyte cancer in patients with history of BCC. There is early evidence from a small trial that oral nicotinamide may reduce the risk for subsequent keratinocyte carcinoma in nonimmunosuppressed individuals with a history of such Table XIII.…”
Section: Follow-up and Reducing Risk For Future Skin Cancersmentioning
confidence: 99%
“…[116][117][118][119]123,[125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141] …”
Section: Follow-up and Reducing Risk For Future Skin Cancersunclassified